Multiple environmental exposures and obesity in eastern China: An individual exposure evaluation model. (July 2022) - Li, Guoao; Liu, Jianjun; Lu, Huanhuan; Hu, Wenlei; Hu, Mingjun; He, Jialiu; Yang, Wanjun; Zhu, Zhenyu; Zhu, Jinliang; Zhang, Hanshuang; Zhao, Huanhuan; Huang, Fen
Abstract: Obesity has caused a huge burden of disease. Few studies have explored individuals' environmental exposure level and the impact of multiple environmental exposures on obesity. The aim of this study was to explore individual air pollution exposure evaluation, and the association between and multiple environmental factors and obesity among adult residents in rural areas of China. In this study, 8400 residents of 14 districts and counties in eastern of China were selected by multistage stratified cluster sampling, and a total of 8377 residents were included in the final analysis. We adopted BMI (Body Mass Index) > 28 kg/m 2 as the definition of obesity. First, an individual air pollution evaluation model was established based on the monitoring data of air pollution stations closest to residential address, different demographic characteristics of residents and daily living habits using generalized linear model and random forest model. Then, we used Bayesian Kernel Machine Regression (BKMR) and Quantile g-Computation (QgC) models to explore multiple environmental exposures on obesity. The results showed that six air pollutants were significantly positively associated with obesity, and green space had a significant protective effect on obesity. The BKMR model showed that the effects of different air pollutants on obesity were significantly enhanced by each other, while green space significantly reduced the positive effect of air pollution on obesity. The QgC model showed a significant positive association with obesity when all environmental factors were exposed as a whole, especially in males, higher household incomes and young people. It suggested that relevant authorities should improve regional air quality and green space to reduce the burden of disease caused by obesity. Graphical abstract: Image 1 Highlights: We evaluated individual air pollution exposure of residents in Anhui Province. There was a positive association between air pollution and obesity. Green space was negatively associated with obesity. Green space could attenuate effect of air pollution on obesity. Multiple environmental exposure was positively associated with obesity.